Comparative study of agriculture microfinance client and non-client rice farmers' production in San Francisco, Agusan del Sur - Manzano, Gianne Francis Alfred E.
One of the major problems the country is experiencing is poverty. A solution to the problem is the formation of capital empowerment thru microfinance for the agricultural sector. In San Francisco, Agusan del Sur, 96 client and non-client rice farmers were interviewed to answer whether is a difference on the productivity and to answer whether the agriculture microfinance programs respond to the needs, income and improve the capability, profitability ans sustainability of rice farm operations. Using descriptive analysis, it was found out that agriculture microfinance client rice farmers produced more volume of production than the non-client rice farmers. Most of the rice farmers who resorted to avail of loans from the informal sector have fear on the risk they may encounter from formal financial institutions. Furthermore, using the neoclassical second-degree polynomial production function which is analyzed thru Ordinary Least Squares Regression Method, it was found that an addition of the variable agriculture microfinance to the production system can increase productivity of the volume of production. Moreover, the variables which can be improved are the farm area, labor, seeds, fertilizer and crop protection chemicals application productively at certain level. Therefore, microfinance institutions must promote the provision of agriculture microfinance to rice farmers to improve productivity.